Zajištění portfolia při řízení volné likvidity podniku - Tetřevová, Liběna; Makovský, Zdeněk (Univerzita Pardubice, 2009)
The dramatic development of the financial markets in the recent years, related mainly to the development of communications technologies and to globalization, enabled our companies to make easy use of the capital markets to up-value their momentarily surplus dead capital. The reason why our companies have not used this possibility so much so far is partly the tradition of using banking institutions, partly the historically not very developed financial market, and last but not least the worries about the risk of money depreciation. This article deals with the risk management in relation to portfolio in condition of the Czech Republic (as transformed economy).
Keywords: Risks; portfolio; hedging; financial instruments; financial derivatives